Influence of Vertical Integration on Efficiency of Company’s Activity - ЧеркасоваВиктория Артуровна; ЧеркасоваЕлизавета Сергеевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2011)
This article is devoted to the decision-making mechanism of vertical integration at a company level. Different approaches to the analysis of vertical integration transactions, which exist for today, are revealed. The estimation of existing ways of the analysis is given, relationships between the various factors, which influence the general result of vertical integration transactions, are determined.In the article the recommendations for the Russian car industry are given on the basis of the review of the vertically integrated companies, which exist for today, the mathematical model is described, which explains the logic of the firm’s decision of integration.